2022
DOI: 10.1002/ajmg.c.32014
|View full text |Cite
|
Sign up to set email alerts
|

The heart in RASopathies

Abstract: The cardiovascular phenotype associated with RASopathies has expanded far beyond the original descriptions of pulmonary valve stenosis by Dr Jaqueline Noonan in 1968 and hypertrophic cardiomyopathy by Hirsch et al. in 1975. Because of the common underlying RAS/MAPK pathway dysregulation, RASopathy syndromes usually

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 106 publications
0
6
0
Order By: Relevance
“…Recently these drugs have been proposed as potential therapies in NS and related syndromes. 26,27 Marin et al 28 showed that the treatment of NSML mice with rapamycin could prevent the onset of disease or reverse HCM. Recently, an infant with NSML and severe obstructive HCM was treated with everolimus, showing a significant improvement in symptoms and b-type natriuretic peptide levels.…”
Section: Discussionmentioning
confidence: 99%
“…Recently these drugs have been proposed as potential therapies in NS and related syndromes. 26,27 Marin et al 28 showed that the treatment of NSML mice with rapamycin could prevent the onset of disease or reverse HCM. Recently, an infant with NSML and severe obstructive HCM was treated with everolimus, showing a significant improvement in symptoms and b-type natriuretic peptide levels.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in genes associated with RAS signalling are associated with CHD in humans and mice (Araki et al, 2004;Delogu et al, 2022). Consistent with this, according to Bgee multispecies' expression database (version 15.0; accessed 26 October 2023; https:// www.…”
Section: Introductionmentioning
confidence: 61%
“…Mutations in RAS/MAPK cell signalling pathway, or ‘RASopathies’, are associated with PS; these include Noonan and Leopard syndromes (Delogu et al., 2022 ; Tartaglia et al., 2011 ). PRKD1 is also associated with the regulation of RAS signalling (Su et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a cardiac perspective, RASopathies present with hypertrophic heart disease in childhood, commonly characterized by biventricular involvement, end-stage remodeling, frequent heart failure-related hospitalizations, and increased mortality. 11,12 Mitogen-Activated Protein Kinase 1 Inhibitors…”
Section: Rasopathiesmentioning
confidence: 99%